The experimental research of filtration quality of doppler signal spectral structure by modu-lated filter - Baryshev, I.V.; Scherbina, К.А.; Msallam, E.P.; Vonsovitch, M.А.; Odokienko, A.V. (Radiotekhnika, 2017)
The comparative analysis of quantitative assessments of filtering by six performance indices of filter circuits of continuous-wave Doppler signal of 1st order PLL, 2nd order PLL, FLL with narrow-band filter circuit quadrature FM-detector based on synchronized oscillator with forced frequency tuning is carried out. The total average performance indices of the circuit with SG exceeded any of the compared indices by 1.5 times, with a tenfold increase in separate parameters. At the same time the method of indices calculation of filter circuits with SG is developed and simple calculation formulas are obtained.